Pengisian Jabatan Anggota Badan Pemeriksa Keuangan (BPK) Untuk Mewujudkan BPK Yang Independen - Simanjuntak, Dumaria (Jurnal Hukum & Pembangunan, 2017)
BPK as the only external audit institution that is equal to other state institutions whose responsibility to audit the state finance's management and accountability should be far apart from political parties' interests. However nowadays some of the chief-persons of BPK are involved in political parties' interests morever become suspects in some corruption cases. To establish BPK as independent and professional institution, chief-person position charging must be free from political parties' interests. This essay exposes the development of regulation of BPK chief-person position charging as main topic analysis. The conclusion of the research is there was advance development in regulation related to BPK chief-person position charging, in term of mechanism and charging duration.